Looking after persons in old age as a source of dilemmas for family careers - Kotlarska-Michalska, Anna (Problemy społeczne: Trwałość i zmienność w dynamicznej rzeczywistości. Księga jubileuszowa z okazji 45-lecia pracy naukowej i dydaktycznej Profesor Jolanty Grotowskiej-Leder, 2022)
This study still deals with the current issues of care provided to the elderly by family caregivers who experience many dilemmas related to the selection of the most effective forms of care, adequate to their own physical, mental and organizational abilities. The study highlights several important types of dilemmas experienced by family caregivers who have to deal with the role of a caregiver on their own. These dilemmas cannot always be resolved by them on their own and require system solutions. The author of the study, while reviewing the state of knowledge about the specificity of the role of an elderly caregiver, also indicated areas of ignorance about the scale of difficulties faced by family caregivers of elderly people in Poland.